Contemporary South African Art 1985-1995 from the South African National Gallery Permanent collection. - Bedford, Emma; Martin, Marilyn; South African National Gallery, Cape Town (Cape Town : South African National Gallery, 1996)
Ainslie, bill ; Alexander, Jane ; Appollis, Tyrone ; Arnott, Bruce ; Arnott, Lauryn ; Atkinson, Kevin ; Badenhorst, Philip ; Ballot, Titia ; Bardavid, Reggi ; barker, Wayne ; Bauer, Derek ; Bell, Deborah ; et al.
South African National Gallery, Cape Town. 14.12.1996-31.3.1997
kunstcatalogus
Keywords: Zuid Afrika